Oncologic outcome in surgical management of jugular paraganglioma and factors influencing outcomes - Raja Lope Ahmad, Raja Ahmad Al'konee; Sivalingam, Shailendra; Konishi, Masaya; De Donato, Giuseppe; Sanna, Mario (Wiley Periodicals, 2013)
Background. The purpose of this study was to identify the factors that may influence the management outcome in patients with jugular paragangliomas. Methods. The surgical records of 121 cases of jugular paraganglioma(Fisch classifications C and D) were reviewed. Results. The average follow-up was 88 months. Intracranial extension (ICE; Fisch classification De and Di) constitutes 55.4% of the cases. Two cases had a malignant jugular paraganglioma. Complete tumor resection was achieved in 81.8% of the cases, and there was evidence of recurrence in 4.0% from this group. Surgical tumor control was achieved in 96% of cases. Perioperative complications consisted mainly of cerebrospinal fluid leakage in 1.6% of the cases. The lower cranial nerve (CN) was preserved in 63% of the patients mainly in the cases without ICE. Conclusion. The infratemporal fossa approach type A allows for complete tumor resection with low perioperative morbidity and recurrence rates. The significant influential factors were the severity of ICE and internal carotid artery involvement.